Enabling or enfeebling the private sector? Government policy responses and business initiatives during COVID-19 - Rosenbach, Gracie; Resnick, Danielle (International Food Policy Research Institute, 2020)
The economic effects of the COVID-19 pandemic — at the global, country, and household levels — are dramatic, plunging the world into a recession not experienced in more than a half century (World Bank 2020a). Unlike other recent global crises, such as the food price crisis (2007–2008) or the financial crisis (2008), the pandemic has affected businesses across all industries and sectors, from agriculture to manufacturing to tourism, services, and mining. At the same time, it is spurring new innovations in response to public health needs and technological advances. This policy brief uses data from the COVID-19 Policy Response (CPR) Portal to examine trends in how government COVID-19 response policies have hindered or promoted the private sector, as well as the private sector’s role in combatting the pandemic. Comparing these policies and responses can provide useful insights into best practices for balancing the twin goals of economic and public health during a crisis.